Prostaglandins in Cancer Cell Adhesion, Migration, and Invasion. (29th February 2012) - Menter, David G.; DuBois, Raymond N.
Abstract : Prostaglandins exert a profound influence over the adhesive, migratory, and invasive behavior of cells during the development and progression of cancer. Cyclooxygenase-2 (COX-2) and microsomal prostaglandin E2 synthase-1 (mPGES-1) are upregulated in inflammation and cancer. This results in the production of prostaglandin E2 (PGE2 ), which binds to and activates G-protein-coupled prostaglandin E 1 – 4 receptors (EP 1 – 4 ). Selectively targeting the COX-2/mPGES-1/PGE2 /EP 1 – 4 axis of the prostaglandin pathway can reduce the adhesion, migration, invasion, and angiogenesis. Once stimulated by prostaglandins, cadherin adhesive connections between epithelial or endothelial cells are lost. This enables cells to invade through the underlying basement membrane and extracellular matrix (ECM). Interactions with the ECM are mediated by cell surface integrins by "outside-in signaling" through Src and focal adhesion kinase (FAK) and/or "inside-out signaling" through talins and kindlins. Combining the use of COX-2/mPGES-1/PGE2 /EP 1 – 4 axis-targeted molecules with those targeting cell surface adhesion receptors or their downstream signaling molecules may enhance cancer therapy.